PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP LOYALITAS PT. PEGADAIAN UNIT PELAYANAN CABANG BABURA - Marbinoto, Mayono Suko; Purba, Johana Sihol Marito (LPPM ISTP, 2024)
The tcount value is 0.065 while the ttable is 1.662 and is significant at 0.065, so that the tcount is 0.065 < ttable 1.662 and is significant 0.000 < 0.05, then H2 is accepted and H0 is rejected, which states that Service Quality has a positive and significant effect partially towards the Loyalty of PT Pegadaian Service Unit Babura Branch. The Fcount value is 11,706 while the Ftable is 2.711 which can be seen at α = 0.05 (see attached table F). The significant probability is much smaller than 0.05, namely 0.000 < 0.05, so the regression model can be said that simultaneously in this research Promotion and Service Quality have a positive and significant effect on the Loyalty of PT Pegadaian Service Unit Babura Branch. Promotion and Service Quality also has a very close relationship with Customer Loyalty with an R value of 0.196. Apart from that, 80.4% of PT Pegadaian Service Unit Babura Branch Customer Loyalty. can be explained by promotions and service quality, while the rest can be explained by other factors.